Olecranon bone grafting in neglected forearm fractures - Jose, Ashish Kumar; R., Surendher Kumar (International Surgery Journal, 2016)
Background: Autogenous bone grafts are widely used to augment union in fractures. Of all the available donor sites, the iliac bone grafts are the most commonly used. Olecranon bone grafts are rarely used to augment union in long bone fractures along with plate osteosynthesis. Methods: Twenty patients of which 18 were male and 2 were female with 9 injuring their right side and 11 injuring their left side, were treated in Mahatma Gandhi Medical College, Pillaiyarkuppam, Pondicherry, India, during the period from January 2012 to December 2014. The fractures were classified as neglected if the duration was more than 4 weeks after the injury. The reason for delay in seeking treatment was indigenous treatment by native bone setters. Results: All had complete union at an average of 3 months (2 and half - 4 months). All had complete range of elbow and wrist flexion and extension by 1 month. No patient complained of bone graft donor site pain. The outcome was excellent and all the fractures united at an average time of 3 months. There was no donor site morbidity. Conclusions: Despite lack of popularity, olecranon bone grafts are an excellent option for augmenting union in fractures of the forearm as these grafts are easily obtained and cause no donor site complications.